DAPAM 20-271 1959 : German northern theater of operations, 1940-1945. - Ziemke, Earl F. (Washington, DC : Department of the Army, Headquarters, 1959)
This volume describes two campaigns that the Germans conducted in their northern theater of operations. The first they launched, on 9 April 1940, against Denmark and Norway. The second they conducted out of Finland in partnership with the Finns against the Soviet Union. The document is divided into two sections. Part I describes the campaigns in Norway and Denmark (background of German operations, landings, plans, operations in southern/central/northern Norway, and the campaign in Norway). Part II details operations in Finland (plans and preparations, Operation Silberfuchs, Finland’s War, the northern theater in 1942, etc.).